The formula for the quadratic formula is x (c in this case) = (-b(+/-)√(b²-4ac))/2a
This is used for an equation in standard quadratic form: ax² + bx + c = 0
1.) Put it in the correct form, if not already in it.
Ex. c² + 6c + 8 = 0
2.) Identify each part of the equation:
a = 1 (the leading coefficient), b = 6 (the coefficient in front of the second variable), c = 8
3.) Plug in each variable answer
c = (-6(+/-)√(6²-4(1)(8))/2(1)
4.) Simplify
c = (-6(+/-)√(36-(4*8))/2
c = (-6(+/-)√(36-32))/2
c = (-6(+/-)√(4))/2
c = (-6(+/-)2)/2
*Here, the equation splits in two. It becomes:
c = (-6+2)/2 AND c = (-6-2)/2
*Simplify again:
c = -4/2 AND c = -8/2
c = -2 AND c = -4
The answers c = -2 and c = -4 would solve the given equation.
Hope this helps! :)
Answer: idk the answer but i can tell u that u are trying to find the value of the symbols and the numbers :)
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
If you have to add 2 to X to get it back to the original, it started out 2 to the left. (It would seem like it ought to be C, but when you add an subtract from the x value in functions, it's opposite of what you might think.)
Answer:
74
Step-by-step explanation:
Answer:
the order is Paco, Tim, Jenny, Maria
Step-by-step explanation: